Distributed MD5 Brute Force Using Message Passing Interface (MPI) on ARM Architecture - Saputra, Maulana Bagus; Umam, Chaerul (Jurnal Transformatika, 2023)
Over the years, there has been a computing paradigm shift towards smart devices. However, the security aspect of this type of device is questionable. In this research, the writer provides a design, implementation, and testing of a distributed MD5 brute-force attack method. Testing is performed using two systems. The first system is an ARM Cluster consisting of four single-board computers. The second system is a conventional server with two Xeon processors. From this research, the writer wants to answer the question of whether distributed brute-force attacks using IoT nodes can be realized in the real world by doing a comparison between increases of ARM Cluster performance with node addition to conventional server performance. From the test result, Xeon model performance is equivalent to 8 ARM Clusters and around 30 ARM nodes are required to match Xeon model performance.